2023
DOI: 10.1038/s41392-023-01654-7
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional mesoporous silica nanoparticles for biomedical applications

Bolong Xu,
Shanshan Li,
Rui Shi
et al.

Abstract: Mesoporous silica nanoparticles (MSNs) are recognized as a prime example of nanotechnology applied in the biomedical field, due to their easily tunable structure and composition, diverse surface functionalization properties, and excellent biocompatibility. Over the past two decades, researchers have developed a wide variety of MSNs-based nanoplatforms through careful design and controlled preparation techniques, demonstrating their adaptability to various biomedical application scenarios. With the continuous b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(11 citation statements)
references
References 514 publications
0
11
0
Order By: Relevance
“…These characteristics make MSNs highly attractive for drug delivery applications, as they offer excellent biocompatibility, biosafety, control of biodegradation and high drug loading capacity. 97 The evidence from cellular and animal studies have confirmed the sustained release properties of MSNs for intraocular pharmacotherapy. 98 Moreover, animal experiments have demonstrated the ability of MSNs to effectively deliver drugs to the anterior chamber of the eye through the cornea.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 87%
“…These characteristics make MSNs highly attractive for drug delivery applications, as they offer excellent biocompatibility, biosafety, control of biodegradation and high drug loading capacity. 97 The evidence from cellular and animal studies have confirmed the sustained release properties of MSNs for intraocular pharmacotherapy. 98 Moreover, animal experiments have demonstrated the ability of MSNs to effectively deliver drugs to the anterior chamber of the eye through the cornea.…”
Section: Mesoporous Silica Nanoparticlesmentioning
confidence: 87%
“…This capability is particularly beneficial in targeting diseases where localized and prolonged drug delivery is needed. Additionally, MSNs are recognized for their biocompatibility and potential for surface modification, making them ideal candidates for targeted drug delivery systems that aim to reduce systemic side effects and enhance treatment efficacy [ 97 , 98 , 99 , 100 ]. These systems, as detailed in studies such as those by Zhu et al [ 30 ], have demonstrated significant improvements in delivering antitubercular drugs, such as INH and RFP, directly to the infected bone tissue.…”
Section: Nanotechnology In Bone Tuberculosis Treatmentmentioning
confidence: 99%
“…In addition, mesoporous silica NPs have been proven to have excellent biocompatibility and to significantly decrease unwanted reactions and cytotoxicity, which are the main issues in the case of carrier materials. Their inert nature and stability in physiological environments increases their suitability for in vivo applications, allowing targeted delivery to inflamed sites without compromising systemic safety [ 110 ].…”
Section: Immunomodulatory Strategies In Drug Deliverymentioning
confidence: 99%